To your health : how to understand what research tells us about risk - Kraemer, Helena Chmura (Oxford University Press, 2005)
The public is bombarded daily with reports about risk factors, many conflicting with each other, other accepted as "scientific truth" for awhile, then scientifically disproved, yet others questionable that later prove to be true. Physicians are faced with trying to make sense of those conflicting or questionable results in the scientific literature in order to guide their patients to the best possible decisions. The situation is not much easier for scientists who may waste years of their productive life, and considerable resources, basing their research efforts on what prove to be misleading earlier research findings. What this book does is to present, in non "academese" and with many examples from the general media and scientific journals, a guide to a critical reading of research reports, which, in turn, serves as a guide to researchers as to which approaches are likely to be regarded with raised eyebrows, and what they need to do to generate results that will be take seriously. This stimulating and helpful book was written for informed consumers and physicians as well as for scientists evaluating the risk research literature or contemplating projects on risk research.